2019
DOI: 10.1002/cpe.5268
|View full text |Cite
|
Sign up to set email alerts
|

A parallel tree node splitting criterion for fuzzy decision trees

Abstract: Fuzzy decision trees are one of the most important extensions of decision trees for symbolic knowledge acquisition by fuzzy representation. Many fuzzy decision trees employ fuzzy information gain as a measure to construct the tree node splitting criteria. These criteria play a critical role in the construction of decision trees. However, many of the criteria can only work well on small-scale or medium-scale data sets, and cannot directly deal with large-scale data sets on the account of some limiting factors s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…On the basis of traditional fuzzy decision tree, many improved fuzzy decision trees are produced, they all optimize the process of data fuzziness, for example, Junhai Zhai , Xizhao Wang et al proposed a fuzzy decision tree based on tolerance rough fuzzy sets [11]. By fuzzizing data based on tolerance rough fuzzy sets, the efficiency of fuzzification can be improved and the loss of information can be reduced, Yashuang Mu, Lidong Wang and Xiaodong Liu proposed A parallel tree node splitting criterion for fuzzy decision trees [12], they design a parallel tree nodesplitting criterion (MR-NSC) based on fuzzy information gain via MapReduce, which is completed equivalent to the traditional unparallel splitting rule, this new method makes the fuzzy decision tree break through the limitation of algorithm complexity and still have good performance on big data, they also designed a fuzzy project division criterion based on dynamic programming under the framework of fuzzy decision tree induction [13].…”
Section: Introductionmentioning
confidence: 99%
“…On the basis of traditional fuzzy decision tree, many improved fuzzy decision trees are produced, they all optimize the process of data fuzziness, for example, Junhai Zhai , Xizhao Wang et al proposed a fuzzy decision tree based on tolerance rough fuzzy sets [11]. By fuzzizing data based on tolerance rough fuzzy sets, the efficiency of fuzzification can be improved and the loss of information can be reduced, Yashuang Mu, Lidong Wang and Xiaodong Liu proposed A parallel tree node splitting criterion for fuzzy decision trees [12], they design a parallel tree nodesplitting criterion (MR-NSC) based on fuzzy information gain via MapReduce, which is completed equivalent to the traditional unparallel splitting rule, this new method makes the fuzzy decision tree break through the limitation of algorithm complexity and still have good performance on big data, they also designed a fuzzy project division criterion based on dynamic programming under the framework of fuzzy decision tree induction [13].…”
Section: Introductionmentioning
confidence: 99%
“…According to the proportion of times of each frequency, it is found that the retention rate of members who use the PC terminal to initiate online video access requests is higher than that of members on the mobile terminal or iPad terminal, and the video conversion rate is lower in the viewing process, that is, less than 5% of users have switched videos in the viewing process (Jan et al) [ 11 ]. The author of this article further clustered the video conversion time initiated by members and found that most of the video conversion time was when the frequency began to play (Mu et al) [ 12 ]. Finally, according to the above collected data and the law of analysis from the data, we can do the user experience research and evaluation model of the online video education mode.…”
Section: Related Workmentioning
confidence: 99%